2022
DOI: 10.1159/000528019
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib and Bruton’s Tyrosine Kinase Inhibitors in Chronic Lymphocytic Leukemia: Focus on Atrial Fibrillation and Ventricular Tachyarrhythmias/Sudden Cardiac Death

Abstract: Background: The natural history of chronic lymphocytic leukemia (CLL) was dramatically improved by the introduction of ibrutinib, a Bruton’s kinase (BTK) inhibitor. In this review we aimed to summarize and critically evaluate the association between first and second generation BTK inhibitors and the risk of atrial fibrillation (AF) and ventricular arrhythmias (VA). Summary: Since the first clinical experience, the development of AF was observed as the result of off-target effects that likely combined with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Following an 8-year follow-up, it was found that ibrutinib reduced all-cause mortality, and produced few cases of ventricular arrhythmias and sudden cardiac death, independently of QT lengthening (28). In the case that AEs occur, both the reduction of the dose of ibrutinib and the careful management of arrhythmia can allow for long-term treatment and reduce all-cause mortality with a prolonged PFS and a reduced all-cause mortality (30).…”
Section: Covalent Btkismentioning
confidence: 99%
“…Following an 8-year follow-up, it was found that ibrutinib reduced all-cause mortality, and produced few cases of ventricular arrhythmias and sudden cardiac death, independently of QT lengthening (28). In the case that AEs occur, both the reduction of the dose of ibrutinib and the careful management of arrhythmia can allow for long-term treatment and reduce all-cause mortality with a prolonged PFS and a reduced all-cause mortality (30).…”
Section: Covalent Btkismentioning
confidence: 99%
“…Treatment with BTK inhibitors in continuous monotherapy may not be optimal, as most responses are PRs and only the minority of patients achieve CR ( 64 ). There are long-term safety concerns including cardiac events and the risk of rapid progression following BTKi cessation ( 65 , 66 ). Some patients might find the ongoing need for therapy unacceptable and difficult to comply in real-life scenarios.…”
Section: Zanubrutinib – Approved Indicationsmentioning
confidence: 99%
“…Despite the small number of investigations that have drawn attention to VAs associated with ABR [ 13 , 14 ], its impact on VA remains inadequately assessed and the underlying mechanisms of ABR-induced VAs remain unclear. Our group has demonstrated that acute as well as chronic IBR treatments are associated with the aberration of membrane voltage and intracellular calcium (Ca 2+ ) dynamics in the heart, with a subsequent increase in VA vulnerability [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%